2023
DOI: 10.1038/s41598-023-30380-x
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a cynomolgus macaque grimace scale for acute pain assessment

Abstract: Cynomolgus macaques may undergo surgical procedures for scientific and veterinary purposes. Recognition and assessment of pain using validated tools is a necessary first step for adequately managing pain in these primates. Grimace scales are one means of assessing the occurance of acute pain using action units such as facial expressions and posture. The aim of this study was to create and validate a Cynomolgus Macaque Grimace Scale (CMGS). Cynomolgus macaques (n = 43) were video recorded before and after a sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 86 publications
0
4
1
Order By: Relevance
“…Contrary to our results, previous research reported observer's gender bias in whole-body behavior pain scales for cats 34,62 and dogs 62 , as well as macaque 13 , sow 28 , and donkey 23 grimace scales. In surveys of veterinarians' attitudes, women assigned higher pain levels than men for different surgical procedures in dogs and cats [52][53][54] .…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Contrary to our results, previous research reported observer's gender bias in whole-body behavior pain scales for cats 34,62 and dogs 62 , as well as macaque 13 , sow 28 , and donkey 23 grimace scales. In surveys of veterinarians' attitudes, women assigned higher pain levels than men for different surgical procedures in dogs and cats [52][53][54] .…”
Section: Discussioncontrasting
confidence: 99%
“…In the last 30 years, scientists created grimace scales to assess pain in a wide variety of mammals, such as humans [10][11][12] , macaques 13 , mouses 14 , rats 15 , rabbits 16 , cats 17 , horses [18][19][20][21] , donkeys 22,23 , ferrets 24 , sheep 25,26 , and pigs 27,28 . Several pain scales have also been developed considering the whole-body behavior in non-human mammals, such as rats 29 , rabbits 30 , cats [31][32][33][34] , dogs 35 , horses 19,21,36,37 , donkeys 38 , cattle 39,40 , sheep 41,42 , goats 43 , and pigs 44,45 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main difference is that the EWAG focuses on assessing welfare at the individual level and monitoring cumulative suffering over time based on research use, whereas the PWAT is focused on assessing the overall primate behavioural management programme. Primates in research are used for more long-term studies compared to other research species, further emphasising the importance of a multifaceted approach to assessing welfare over time and considering cumulative suffering (Honess & Wolfensohn 2010 ; Paterson et al 2023 ). Using a broader tool such as the PWAT could help identify gaps in the primate management programme that could result in animal-based indicators of poor welfare or cumulative suffering, while implementing a purely animal-based measure of welfare, such as the EWAG, could be used to monitor specific at-risk animals based on procedural severity and cumulative use, which could then be used to make decisions on humane endpoints (Honess & Wolfensohn 2010 ; Nunamaker et al 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The identification and management of pain, whether spontaneous, perioperative, or related to research manipulations, is key to optimizing the welfare of marmosets engaged in biomedical research. The development and validation of a pain scoring system such as that described for cynomolgus macaques in Paterson et al would enhance the ability of marmoset users to adequately manage perioperative and spontaneous pain in marmosets [ 42 ]. The author encourages the use of a facility-specific pain assessment tool, especially for postoperative pain management, that can be updated as more evidence-based guidelines are published.…”
Section: Veterinary Carementioning
confidence: 99%